Generation of electric power and air conditioning by cogeneration: a proposal for energy saving - Vera-Romero, Iván (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper presents the results of a case study carried out in a warehouse, and, in particular, the technical data obtained from field visits and a proposal for energy saving. The proposal entails incorporating a cogeneration system based on a motor generator (400 kWe ISO) to produce electrical energy, and an absorption cooling system (75 TR) that uses residual heat to generate air-conditioning. The absorption chiller consumed 54% less energy than the conventional air-conditioning system. Moreover, the produced energy can supply the plant’s total consumption, in addition to offering an excess of 57,312 kWh per month, which was reflected in the analysis of energy for sale to users with a high domestic consumption rate (DAC, for its Spanish acronym). The proposal’s total investment is USD 1,091,258, with a net monthly savings of USD 30,901, and an investment payback period of 2.9 years, which indicates the viability of this project according to its energy characteristics, notwithstanding that it is for a service provider company.